Health (il)literacy: Structural vulnerability in the nurse navigator service. Issue 2 (8th July 2021) - Byrne, Amy‐Louise; Harvey, Clare; Baldwin, Adele
Abstract: Health literacy is a contemporary term used in health services, often used to describe individuals requiring additional support to access, understand and implement health service information. It is used as a measure of self‐efficacy in chronic disease models of care such as the nurse navigator service. The aim of the research was to investigate the concept of health literacy in the nurse navigator service, particularly in relation to the defined role objective of person‐centred care. Fairclough's critical discourse analysis was used to analyse the experiential, relational and expressive elements of texts, investigating the hidden truths which are represented in discourse. Texts from a variety of health service micro‐, meso‐ and macro‐hierarchical sources were selected for analysis using the nurse navigator evaluation data set and other associated texts. Health literacy in the nurse navigator service is a technology of government used to increase participation of individuals in their own health and well‐being. The discourse suggests that health literacy responsibilises both individuals and nurses and is discursively formed within a matrix of rational choice. In this context, health literacy contributes to structural vulnerability.